2014
DOI: 10.3389/fnhum.2014.00219
|View full text |Cite
|
Sign up to set email alerts
|

Indestructible plastic: the neuroscience of the new aging brain

Abstract: In recent years, research on experience-dependent plasticity has provided valuable insight on adaptation to environmental input across the lifespan, and advances in understanding the minute cellular changes underlying the brain’s capacity for self-reorganization have opened exciting new possibilities for treating illness and injury. Ongoing work in this line of inquiry has also come to deeply influence another field: cognitive neuroscience of the normal aging. This complex process, once considered inevitable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 142 publications
(179 reference statements)
0
5
0
1
Order By: Relevance
“…These factors, when viewed in conjunction with the antecedents of chronic disease, such as diabetes, cardiovascular diseases, obesity and metabolic syndrome, point to possibilities for optimism for a healthier aging brain. Health effects associated with these chronic diseases may be modifiable through changes aiming at increasing physical activity/decreasing sedentary lifestyles, better stress management and participation in meaningful social networks, leading to a decrease in comorbidities and thus a healthier aging brain (Berchicci et al, 2014;Bodde et al, 2013;Daffner, 2010;Dunton et al, 2009;Holman and de Villers-Sidani, 2014;Pinazo-Duran et al, 2014;Piniewski et al, 2011;Puska, 2009;Spiro and Brady, 2011;Topiwala and Ebmeier, 2012;Voss et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These factors, when viewed in conjunction with the antecedents of chronic disease, such as diabetes, cardiovascular diseases, obesity and metabolic syndrome, point to possibilities for optimism for a healthier aging brain. Health effects associated with these chronic diseases may be modifiable through changes aiming at increasing physical activity/decreasing sedentary lifestyles, better stress management and participation in meaningful social networks, leading to a decrease in comorbidities and thus a healthier aging brain (Berchicci et al, 2014;Bodde et al, 2013;Daffner, 2010;Dunton et al, 2009;Holman and de Villers-Sidani, 2014;Pinazo-Duran et al, 2014;Piniewski et al, 2011;Puska, 2009;Spiro and Brady, 2011;Topiwala and Ebmeier, 2012;Voss et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…38 In recent years, there is a growing interest in computer-based cognitive training as an effective way of enhancing cognition and neural plasticity in older adults. 39 Overall, the results indicated that the participants did not significantly improve their specific-attentional function and global cognitive function (total score of MMSE and MoCA) after receiving multidomain attention training. However, the participants showed changes in some domains of global cognitive measurement (ie, MMSE and MoCA subcomponents).…”
Section: Discussionmentioning
confidence: 84%
“…Fortunately, the older brain retains plasticity abilities, and as such, cognitive training and exercise may help reduce the negative effects of age on attention . In recent years, there is a growing interest in computer‐based cognitive training as an effective way of enhancing cognition and neural plasticity in older adults …”
Section: Discussionmentioning
confidence: 99%
“…Neuronale Plastizität beschreibt ein sich in unterschiedlichen Phänomenen manifestierendes Potential des Nervensystems, sich über die gesamte Lebenszeit des Organismus auf unterschiedlichen Ebenen in Relation zu verschiedensten jeweiligen Beanspruchungen in Funktionsabläufen und Morphologie seiner Organisation dauerhaft zu verändern (Sagi et al, 2012;Holman & Villers-Sidani, 2014). Im neurowissenschaftlichem Kontext dominiert der enger gefasste Begriff der neuronalen Plastizität.…”
Section: 32unclassified